ChemInform Abstract: Officinatrione: An Unusual (17S)‐17, 18‐seco‐Lupane Skeleton, and Four Novel Lupane‐Type Triterpenoids from the Roots of Taraxacum officinale. Issue 27 (13th June 2013) - Saeki, Daisuke; Yamada, Takeshi; In, Yasuko; Kajimoto, Tetsuya; Tanaka, Reiko; Iizuka, Yota; Nakane, Takahisa; Takano, Akihito; Masuda, Kazuo
Abstract Five new lupane‐type triterpenoids, (I)‐(IV), are isolated from the root of dandelion T.